[4-Iodo-3-(isopropylcarbamoyl)phenoxy]acetic Acid as a Highly Reactive and Easily Separable Catalyst for the Oxidative Cleavage of Tetrahydrofuran-2-methanols to γ-Lactones - Yakura, Takayuki; Fujiwara, Tomoya; Nishi, Hideyuki; Nishimura, Yushi; Nambu, Hisanori (Synlett, 2018)
[4-Iodo-3-(isopropylcarbamoyl)phenoxy]acetic acid was developed as a highly reactive and easily separable catalyst for the oxidative cleavage of tetrahydrofuran-2-methanols to γ-lactones in the presence of Oxone® (2KHSO5·KHSO4·K2SO4) as the co-oxidant. The reactivity of this new catalyst was considerably greater than that of our previously reported catalyst, 2-iodo-N-isopropylbenzamide. The new catalyst and product were easily separated by only liquid–liquid separation without chromatography. In addition, using a mixture of nitromethane and N,N-dimethylformamide as the solvent and heating enabled a low catalyst loading, a short reaction time, and high product yield. Oxidative cleavage using the new catalyst can be used as a practical and efficient method for synthesizing γ-lactones.
Keywords: hypervalent iodine; iodobenzamide; organic catalysis; oxidative cleavage; Oxone®